Control of Supplement Logistics in Gyms: A web system for inventory management - Pantoja Pajayo, Fernando Olivert (2025)
This research work presented the administrative problems that a gym presents related to the inefficiency of organizing all the products that arrive at the warehouse and the complexity of managing stocks without a system to control the gym's inventory, also there is a low level of satisfaction of gym customers with respect to the way product information is managed. This study had a quasi-experimental approach to measure the application of the system, as well as a descriptive and explanatory role. The implementation of a web administrative management system in a gym seeks to improve and optimize the registration and stocks of products in the system so that this information can be used in the sales area efficiently and accurately, through the construction of the system. web using the Laravel 11 framework for the backend and Vue.js 3.4 for the fronted, in addition MySQL 8.1 was used as a database manager, using the agile Scrum methodology and the application of qualitative measurement instruments such as the survey and quantitative. such as measurement by direct observation. The measurement results were processed using the pretest, posttest method, using R .4.4.1 for the respective statistical calculations; of which it is considered that the times to manage the stock and the time to obtain the inputs and outputs of inventories were reduced, while the worker satisfaction increased, with a confidence of 95%, reaching the conclusion of that administrative stock management is correctly streamlined.